2017
DOI: 10.1186/s12882-017-0557-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the utility and scalability of a telehomecare intervention for patients with chronic kidney disease undergoing peritoneal dialysis—a study protocol

Abstract: BackgroundChronic Kidney Disease (CKD) is a pressing global health concern that is placing increased strain on health care resources. CKD patients regularly receive peritoneal dialysis as a common CKD treatment. An emerging technological solution is telehomecare as way to support patients receiving PD in their homes. This study protocol outlines a mixed methods evaluation exploring a telehomecare developed to enhance CKD patients’ outcomes and experiences. The study aims to assess the usability, acceptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Some studies [ 15 20 ] have carried out a usability assessment of systems focused on remote monitoring and control of patients with CKD on PD treatment. In [ 17 ], a possible study protocol was introduced, which evaluates the utility and scalability of a telemedicine system for patients with CKD. However, the study did not include results considering a case study in a real scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [ 15 20 ] have carried out a usability assessment of systems focused on remote monitoring and control of patients with CKD on PD treatment. In [ 17 ], a possible study protocol was introduced, which evaluates the utility and scalability of a telemedicine system for patients with CKD. However, the study did not include results considering a case study in a real scenario.…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative study design [26] was employed as part of a larger evaluation of the eQ Connect™ (eQOL Inc.) intervention that includes a parallel-arm randomized, controlled trial (RCT). The aim of the RCT was to determine if utilizing a virtual care solution that included remote monitoring software (eQConnect™) improves selected clinical outcomes for PD patients (CONNECT Trial).…”
Section: Methodsmentioning
confidence: 99%
“…A 2017 meta-analysis concluded that telemedicine reduced admission, shortened length of stay and reduced mortality in patients with congestive heart failure [ 54 ]. Further research is required in the field of telenephrology and dialysis, with upcoming trials such as Clinical Evaluation of Remote Notification to Reduce Time to Clinical Decision (CONNECT) [ 55 ] hopefully gleaning more evidence on objective outcomes to support this ever-growing field.…”
Section: Dialysismentioning
confidence: 99%